Safety and long-term immunogenicity of the two-dose heterologous Ad26.ZEBOV and MVA-BN-Filo Ebola vaccine regimen in adults in Sierra Leone: a combined open-label, non-randomised stage 1, and a randomised, double-blind, controlled stage 2 trial. Issue 1 (January 2022) - Ishola, David; Manno, Daniela; Afolabi, Muhammed O; Keshinro, Babajide; Bockstal, Viki; Rogers, Baimba; Owusu-Kyei, Kwabena; Serry-Bangura, Alimamy; Swaray, Ibrahim; Lowe, Brett; Kowuor, Dickens; Baiden, Frank; et al.
Summary: Background: The Ebola epidemics in west Africa and the Democratic Republic of the Congo highlight an urgent need for safe and effective vaccines to prevent Ebola virus disease. We aimed to assess the safety and long-term immunogenicity of a two-dose heterologous vaccine regimen, comprising the adenovirus type 26 vector-based vaccine encoding the Ebola virus glycoprotein (Ad26.ZEBOV) and the modified vaccinia Ankara vector-based vaccine, encoding glycoproteins from Ebola virus, Sudan virus, and Marburg virus, and the nucleoprotein from the Tai Forest virus (MVA-BN-Filo), in Sierra Leone, a country previously affected by Ebola. Methods: The trial comprised two stages: an open-label, non-randomised stage 1, and a randomised, double-blind, controlled stage 2. The study was done at three clinics in Kambia district, Sierra Leone. In stage 1, healthy adults (aged ≥18 years) residing in or near Kambia district, received an intramuscular injection of Ad26.ZEBOV (5 × 10 10 viral particles) on day 1 (first dose) followed by an intramuscular injection of MVA-BN-Filo (1 × 10 8 infectious units) on day 57 (second dose). An Ad26.ZEBOV booster vaccination was offered at 2 years after the first dose to stage 1 participants. The eligibility criteria for adult participants in stage 2 were consistent with stage 1 eligibility criteria. Stage 2 participants were randomly assigned (3:1), by computer-generated block randomisation (block size of eight) via an interactive web-response system, to receive either the Ebola vaccine regimen (Ad26.ZEBOV followed by MVA-BN-Filo) or an intramuscular injection of a single dose of meningococcal quadrivalent (serogroups A, C, W135, and Y) conjugate vaccine (MenACWY; first dose) followed by placebo on day 57 (second dose; control group). Study team personnel, except those with primary responsibility for study vaccine preparation, and participants were masked to study vaccine allocation. The primary outcome was the safety of the Ad26.ZEBOV and MVA-BN-Filo vaccine regimen, which was assessed in all participants who had received at least one dose of study vaccine. Safety was assessed as solicited local and systemic adverse events occurring in the first 7 days after each vaccination, unsolicited adverse events occurring in the first 28 days after each vaccination, and serious adverse events or immediate reportable events occurring up to each participant's last study visit. Secondary outcomes were to assess Ebola virus glycoprotein-specific binding antibody responses at 21 days after the second vaccine in a per-protocol set of participants (ie, those who had received both vaccinations within the protocol-defined time window, had at least one evaluable post-vaccination sample, and had no major protocol deviations that could have influenced the immune response) and to assess the safety and tolerability of the Ad26.ZEBOV booster vaccination in stage 1 participants who had received the booster dose. This study is registered at ClinicalTrials.gov, NCT02509494 . Findings: Between Sept 30, 2015, and Oct 19, 2016, 443 participants (43 in stage 1 and 400 in stage 2) were enrolled; 341 participants assigned to receive the Ad26.ZEBOV and MVA-BN-Filo regimen and 102 participants assigned to receive the MenACWY and placebo regimen received at least one dose of study vaccine. Both regimens were well tolerated with no safety concerns. In stage 1, solicited local adverse events (mostly mild or moderate injection-site pain) were reported in 12 (28%) of 43 participants after Ad26.ZEBOV vaccination and in six (14%) participants after MVA-BN-Filo vaccination. In stage 2, solicited local adverse events were reported in 51 (17%) of 298 participants after Ad26.ZEBOV vaccination, in 58 (24%) of 246 after MVA-BN-Filo vaccination, in 17 (17%) of 102 after MenACWY vaccination, and in eight (9%) of 86 after placebo injection. In stage 1, solicited systemic adverse events were reported in 18 (42%) of 43 participants after Ad26.ZEBOV vaccination and in 17 (40%) after MVA-BN-Filo vaccination. In stage 2, solicited systemic adverse events were reported in 161 (54%) of 298 participants after Ad26.ZEBOV vaccination, in 107 (43%) of 246 after MVA-BN-Filo vaccination, in 51 (50%) of 102 after MenACWY vaccination, and in 39 (45%) of 86 after placebo injection. Solicited systemic adverse events in both stage 1 and 2 participants included mostly mild or moderate headache, myalgia, fatigue, and arthralgia. The most frequent unsolicited adverse event after the first dose was headache in stage 1 and malaria in stage 2. Malaria was the most frequent unsolicited adverse event after the second dose in both stage 1 and 2. No serious adverse event was considered related to the study vaccine, and no immediate reportable events were observed. In stage 1, the safety profile after the booster vaccination was not notably different to that observed after the first dose. Vaccine-induced humoral immune responses were observed in 41 (98%) of 42 stage 1 participants (geometric mean binding antibody concentration 4784 ELISA units [EU]/mL [95% CI 3736–6125]) and in 176 (98%) of 179 stage 2 participants (3810 EU/mL [3312–4383]) at 21 days after the second vaccination. Interpretation: The Ad26.ZEBOV and MVA-BN-Filo vaccine regimen was well tolerated and immunogenic, with persistent humoral immune responses. These data support the use of this vaccine regimen for Ebola virus disease prophylaxis in adults. Funding: Innovative Medicines Initiative 2 Joint Undertaking and Janssen Vaccines & Prevention BV.